Diagnosis dan Tata Laksana Oftalmia Neonatorum: Tinjauan Pustaka - Suki, Ria Marsela (PT Kalbe Farma Tbk., 2025)
Ophthalmia neonatorum or neonatal conjunctivitis is an acute conjunctivitis in newborns under the age of 1 month. The causes are grouped into aseptic and septic types. Diagnosis is made by clinical symptoms and signs as well as laboratory examination. Appropriate treatment based on etiology can prevent permanent eye damage. Without optimal treatment, complications such as corneal ulceration, perforation, and even blindness may occur.